NICARAGUAN PILGRIMAGE - Ellwood, Gracia Fay (Journal for the study of religion, 1991)
In 1986 the author travelled in Nicaragua as a delegate of Witness for Peace. Afterwards she perceived the journey as a pilgrimage as set forth in the work of Victor Turner. This essay outlines Turner's description and analysis of pilgrimage as a liminal experience, with particular emphasis on communitas and the closeness of the pilgrim to spiritual death and to the sainted dead. The author's experience and that of her fellow delegates in Nicaragua are offered for comparison with Turner's paradigm. Some of the elements in common are a mingling of voluntaryness and compulsion in motivation, dangers and hardships in travel, a strong bond of communitas, and a feeling of participation in the death of a martyr. The result is renewal and commitment to bringing about communitas on a wider scale.